Twenty-one years of using insect resistant (GM) maize in Spain and Portugal: farm-level economic and environmental contributions. Issue 2 (3rd April 2019) - Brookes, Graham
ABSTRACT: This study assesses the economic and environmental impacts that have arisen from the adoption and use of genetically modified (GM) insect resistant (IR) maize in Spain and Portugal in the 21 years since first planted in Spain in 1998. A total of 1.65 million hectares have been planted to maize containing these traits since 1998, with farmers benefiting from an increase in income of €285.4 million. For every extra €1 spent on this seed relative to conventional seed, farmers have gained an additional €4.95 in extra income. These income gains have mostly arisen from higher yields (+11.5% across the two countries using the technology). The seed technology has reduced insecticide spraying by 678, 000 kg of active ingredient (−37%) and, as a result, decreased the environmental impact associated with herbicide and insecticide use on these crops (as measured by the indicator, the Environmental Impact Quotient (EIQ)) by 21%. The technology has also facilitated cuts in fuel use, resulting in a reduction in the release of greenhouse gas emissions from the GM IR maize cropping area and contributed to saving scarce water resources.